Investigation of (Me4N)SCF3 as a Stable, Solid and Safe Reservoir for S=CF2 as a Surrogate for Thiophosgene. Issue 3 (15th December 2017) - Scattolin, Thomas; Pu, Maoping; Schoenebeck, Franziska
Abstract: While thiophosgene finds widespread usage on a multi‐ton scale, its fluorinated counterpart S=CF2 is essentially unexplored in synthesis. Using experimental reactivity tests, ReactIR and computational techniques, we herein showcase that the solid (Me4 N)SCF3 functions as a safe reservoir for S=CF2 . A key feature is that the reactive electrophile is not simply released over time, but instead is liberated under activation with a protic nucleophile. The reactivity of S=CF2 is mild, allowing large‐scale and late‐stage synthetic applications without special reaction control. The mechanism was fully elucidated, including a rationalization of the role of the Me4 N cation and the origins of selectivity. Abstract : Experiments and computations showcase the solid (Me4 N)SCF3 functioning as a safe reservoir for S=CF2 and shed light on the mechanism of activation.